A review on non-isolated low-power DC–DC converter topologies with high output gain for solar photovoltaic system applications. Issue 4 (7th July 2022) - Sutikno, Tole; Purnama, Hendril Satrian; Widodo, Nuryono Satya; Padmanaban, Sanjeevikumar; Sahid, Mohd Rodhi
Abstract: The major challenges of the high-gain DC–DC boost converters are high-voltage stress on the switch, extreme duty ratio operation, diode reverse-recovery and converter efficiency problems. There are many topologies of high-gain converters that have been widely developed to overcome those problems, especially for solar photovoltaic (PV) power-system applications. In this paper, 20 high-gain and low-power DC–DC converter topologies are selected from many topologies of available literature. Then, seven prospective topologies with conversion ratios of >15 are thoroughly reviewed and compared. The selected topologies are: (i) voltage-multiplier cell, (ii) voltage doubler, (iii) coupled inductor, (iv) converter with a coupled inductor and switch capacitor, (v) converter with a switched inductor and switched capacitor, (vi) cascading techniques and (vii) voltage-lift techniques. Each topology has its advantages and disadvantages. A comparison of the seven topologies is provided in terms of the number of components, hardware complexity, maximum converter efficiency and voltage stress on the switch. These are presented in detail. So, in the future, it will be easier for researchers and policymakers to choose the right converter topologies and build them into solar PV systems based on their needs. Abstract : The major challenges of the high-gain DC-DC boost converters are high voltage stress on the switch, extreme duty ratio operation, diode reverse recovery, and converter efficiency problems. Twenty high gain and low power (HGLP) DC-DC converter topologies are selected from many topologies available in the literature. Seven prospective topologies, with conversion ratios >15 times conversion ratio, are compared. Graphical Abstract: